1992
DOI: 10.1136/bmj.304.6839.1401
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of leukaemia and other cancers in birth and schools cohorts in the Dounreay area.

Abstract: Objective-To determine whether a raised incidence of leukaemia in the Dounreay area occurred in children born to local mothers (birth cohort) or in those who moved to the area after birth (schools cohort) and also whether any cases of cancer have occurred in children born near Dounreay who may have moved elsewhere.Design-Foliow up study. Setting-Dounreay area of Caithness, Scotland. Subjects-4144 children born in the area in the period 1969-88 and 1641 children who attended local schools in the same period but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…The results of our cross-sectional analyses indicate that no excesses of childhood and young adult cancer around Sellafield and Dounreay are evident when more recent data covering the period from 1991 to 2006 are considered. Our findings for the earlier time periods (1963–1990) are consistent with earlier published findings ( Black et al , 1992 ; Draper et al , 1993 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of our cross-sectional analyses indicate that no excesses of childhood and young adult cancer around Sellafield and Dounreay are evident when more recent data covering the period from 1991 to 2006 are considered. Our findings for the earlier time periods (1963–1990) are consistent with earlier published findings ( Black et al , 1992 ; Draper et al , 1993 ).…”
Section: Discussionsupporting
confidence: 93%
“…The increased follow-up now available allows investigation of whether the excess cancer risks continue beyond the ages considered by Gardner. Although a similar birth cohort study found no significantly raised risk for children born around the Dounreay site ( Black et al , 1992 ), further investigation of cancer risk beyond age 20 for these individuals is also warranted for comparison.…”
mentioning
confidence: 95%
“…The overall deficit of cancers other than leukaemia and non-Hodgkin's lymphoma is consistent with previous investigations in the Dounreay area. 23 Fourteen cases of cancers other than tumours of the CNS were found in children resident near to Chapelcross compared with 9.25 expected. The MLR test did not reach significance (p=0.073).…”
Section: Discussionmentioning
confidence: 86%
“…For each year, population counts stratified by commune, 5-year age groups and sex were obtained for January 1st. In 2008, Belgium had a population of 10,666,866 inhabitants, divided over the Flemish (6,161,600), Walloon (3,456,775) and Brussels-Capital Region (1,048,491). The smallest administrative level at which age-and sexspecific data are available at the moment in Belgium are the communes.…”
Section: Datamentioning
confidence: 99%